Meningkatkan Kemampuan Bicara dan Menulis pada Lansia Demensia dengan Metode Melukis Kaligrafi Allah + Muhammad - Rizki Dwi Cahyono; Joni Haryanto; Erna Dwi Wahyuni; Wimar Anugrah Romadhon (Politeknik Kesehatan Kemenkes Mamuju, 2020)
Brain changes that occur in the aging process including structure and function make it easier for the elderly to forget new information that they have just received, known as dementia. The right method to improve the symptoms of dementia is by painting the calligraphy